Formulasi sediaan pelembab bibir mengandung ekstrak kulit buah pisang raja (Musa paradisiaca L) - Siregar , Runisya Maugin Utami; Yuniarti, Rafita; Lubis, Minda Sari; Nasution, Muhammad Amin (Journal of Pharmaceutical and Sciences, 2024)
Lip balm is a care product that can keep your lips moist, which is a type of ointment used to treat dry and chapped lips. The benefit of using lip balm for lips is to regulate lip moisture. Lip balms are generally clear or colorless, although recently colored variants have also been created. To find out whether the extract of plantain peel (Musa paradisiaca L) can be formulated in the form of lip balm preparations. The purpose of this study was to determine whether lip balm preparations could be used as moisturizers. To find out lip balm preparations well made and of good physical quality. This research method is experimental. Collection of plants was carried out purposively, ie without comparison with other areas. The sample used was the skin of fresh ripe plantains obtained from the Simpang Limun market in Medan. This study included quality inspection preparations, moisture effectiveness test preparations, irritation tests on formulations and hedonic tests on variations in preparations made. The results of this study indicate that extracts of plantain peel (Musa paradisiaca L) with concentrations of 1%, 3%, 5%, 10%, and 15% can be formulated in the form of lip balm preparations. Formula 5 with a concentration of 15% showed the best lip balm preparation by fulfilling the requirements for physical quality, effectiveness and safety. With a preference value of 5 (like very much), has a melting point of 57'C and has a pH of 5.9 so it does not cause skin irritation and is stable at room temperature storage for 28 days. Lip balm preparations made using cocoa butter base are safe to use and meet the standards..